2014
DOI: 10.2174/1872213x08666140619110657
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Inflammatory and Allergic Responses by Pharmacologically Potent Fungus Ganoderma lucidum

Abstract: Acute inflammation is the result of a complex signal transduction pathway that protects and heals our body and is necessary for our good health and normal wellbeing. Whereas, chronic inflammation can be correlated well with the onset of a plethora of autoimmune disorders; rheumatoid arthritis, systemic lupus and polymyalgia, rheumatic and other diseases like asthma, inflammatory bowel diseases, cardiovascular disorders, ulcerative colitis and Crohn's disease. Also, it has been reported to be associated with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…Ganoderma lucidum has been reported to have wide effects in suppressing inflammation 48 and increases the activity of SOD in cerebral IR 7 . MPO is a characteristic constituent of neutrophil granules and represents ROS-related inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Ganoderma lucidum has been reported to have wide effects in suppressing inflammation 48 and increases the activity of SOD in cerebral IR 7 . MPO is a characteristic constituent of neutrophil granules and represents ROS-related inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…36–38 We have shown that G. lucidum , a key herbal constituent in FAHF-2 and ASHMI, has anti-inflammatory effects on cytokines involved in both allergic and non-allergic disorders. 3941 …”
Section: Discussionmentioning
confidence: 99%
“… 141 In addition, G. lucidum exhibits anti-inflammatory and immunomodulatory effects. 58 The healthy aging mechanism of G. lucidum may be related to Nrf2, mTOR and MAPK pathways. A previous study has shown that G. lucidum treatment induces the expression of Nrf2, while transfection with Nrf2 siRNA attenuates its protection effects.…”
Section: Therapeutic Drugs Targeting Senescencementioning
confidence: 99%